Equity and Equality in Legal Safeguards for the Rights and Duties of Political Party Members: A Normative Analysis - Sultoni Fikri; Reza Maulana Hikam (Mimbar Keadilan, 2025)
This article constitutes an examination of the legal protection of the rights and obligations of political party members, focusing on the crucial role of political party members in maintaining the health and dynamics of the political process. Additionally, this article comprehensively outlines the rights and obligations that govern the behavior of political party members. This research was conducted using the normative legal research method by analyzing primary and secondary legal materials, and applying normative or prescriptive analysis techniques. The analysis results indicate that the rights of political party members include the right to associate, assemble, express opinions, engage in politics, and obtain public office. Meanwhile, the obligations of political party members encompass concrete actions such as practicing Pancasila, upholding state integrity, participating in national development, upholding the supremacy of law, conducting political education, ensuring the success of general elections, and ensuring financial transparency. Furthermore, this article proposes improvements to Law No. 8/2008 in conjunction with Law No. 2/2011 to enhance the protection of the rights and obligations of political party members. This includes the important role of supervisory institutions and law enforcement agencies in safeguarding the rights and obligations of political party members, as well as ensuring compliance with the principles of democracy and the supremacy of law within the scope of political parties. In conclusion, this article provides a significant contribution to understanding the participation, rights, and obligations of political party members in the legal and democratic context of Indonesia.